From Identity to Enaction: Identity Behavior Theory - Simons, Jack D. (Frontiers in Psychology, 2021)
IThe paper deals with the meaning of identity in action regulation. A strengths-based action model, Identity Behavior Theory (IBT), is presented as an action model of behavior concerned with the role that identity plays in the prediction of behavioral enaction, and implications for education, science and clinical practice. With this respect the paper explores and discusses how enacted behavior, including intention and action, depends on level of subscription to identity as well as on resilience and attitudes that are related to such a behavior. The paper also illustrates fields of application of IBT, use of IBT with underrepresented and marginalized groups, and as an instrument for assessing and testing possible effects of resilience, attitudes, and identity on the enacted behavior. IBT is now used to examine behavior in a variety of educational contexts in the United States, and more studies are needed to satisfactorily validate application of the model empirically.